Mass gatherings: a review of the scope for meningococcal vaccination in the Indian context - Anand P Dubey; Rashna Dass Hazarika; Veronique Abitbol; Shafi Kolhapure; Someya Agrawal (Taylor & Francis Group, 2021)
The risk of meningococcal transmission is increased with crowding and prolonged close proximity between people. There have been numerous invasive meningococcal disease (IMD) outbreaks associated with mass gatherings and other overcrowded situations, including cramped accommodation, such as student and military housing, and refugee camps. In these conditions, IMD outbreaks predominantly affect adolescents and young adults. In this narrative review, we examine the situation in India, where the burden of IMD-related complications is significant but the reported background incidence of IMD is low. However, active surveillance for meningococcal disease is suboptimal and laboratory confirmation of meningococcal strain is near absent, especially in non-outbreak periods. IMD risk factors are prevalent, including frequent mass gatherings and overcrowding combined with a demographically young population. Since overcrowded situations are generally unavoidable, the way forward relies on preventive measures. More widespread meningococcal vaccination and strengthened disease surveillance are likely to be key to this approach.